Physical, Chemical, Textural and Sensory Properties of Dried Wheat Noodles Supplemented with Unripe Banana Flour - Pitiporn Ritthiruangdej; Sompit Parnbankled; Sawitri Donchedee; Rungtiwa Wongsagonsup (Agriculture and Natural Resources, 2011)
Unripe banana flour is a starchy food that contains a high proportion of indigestible compounds such as resistant starch, and non-starch polysaccharides, which are included in the dietary fiber content. The objective of this study was to use unripe banana flour as an ingredient to make dried noodle products of high nutritional quality with low carbohydrate digestibility and rich in resistant starch. The effect of wheat flour substitution with unripe banana flour was investigated in terms of the physicochemical, textural, cooking and sensory qualities of dried noodles. Five additional dried noodles were prepared by substituting wheat with 10, 20, 30, 40, and 50% banana flour. The optimal ratio of noodle from banana flour was investigated using sensory qualities in comparison with the control (100% wheat flour). The results of noodle formula development indicated that as the amount of banana flour increased, the stickiness of the noodles decreased and the appearance became darker. The optimum formula consisted of 20.45% banana flour, 47.72% wheat flour, 20.45% water, 2.04% salt, 1.02% sodium carbonate, 6.82% egg powder, 0.14% polyphosphate and 1.36% propylene glycol. Banana flour was used to replace 30% of the total wheat flour in the formula. Uncooked dried noodles were composed of 13.7% protein, 0.12% fat and 4.8% dietary fiber (including 2.8% resistant starch). The optimal cooking time and cooking loss were 14.5 min and 11.15%, respectively. The tensile strength and breaking length of cooked noodles were 16.4 g and 67.2 mm, respectively. The results of consumer evaluation showed that the overall liking of uncooked and cooked dried noodles were at the moderate level. The present study indicated that unripe banana flour is a potential source of fiber when substituted for wheat flour in dried noodle products. The incorporation of 30% unripe banana flour in the noodle ingredients significantly increased their total dietary fiber and resistant starch content.